Morphofunctional changes in gastrointestinal tract of rats due to cafeteria diet (Revista Española de Fisiología, 1992)
Female rats fed a cafeteria diet from birth developed obesity at 60 days of age and their stomach, small intestine and caecum were enlarged when compared with controls, i.e. these regions had greater food storage capacity. In spite of the enlargement, these regions had similar or reduced weight and linear density, which is seen as proof of reduced mechanical performances. Cafeteria diet produced increased glucose duodenal absorption in older animals unlike the typical reduction known in controls. Tryptophan absorption was maintained high in adulthood, compensating for the low structural nutritive properties of the cafeteria diet. The results are interpreted as an adaptation to the cafeteria diet effects and properties: the characteristic overeating of foodstuffs with greater energy density, lower mechanical requirements and lower structural nutritive value than pelleted chow.